Probiotic characterization of Lactobacillus strains isolated from breast milk and employment for the elaboration of a fermented milk product - Carlos Luz; Jorge Calpe; Juan Manuel Quiles; Raquel Torrijos; Máximo Vento; María Gormaz; Jordi Mañes; Giuseppe Meca (Journal of Functional Foods, 2021)
A total of seven strains of lactic acid bacteria (LAB) isolated from breast milk, were investigated for their probiotic properties. Lactobacillus plantarum 5H1 and 5L1 were selected for their beneficial properties and used for probiotic fermented milk manufacture. The fermentation parameters (pH and lactic acid) and LAB viability during fermented milk processing and storage were evaluated. The results showed that the strains had a broad spectrum of antimicrobial activity against pathogenic bacteria and toxigenic fungi. These also evidenced capacity of adhesion and reduction of Salmonella adhesion to Caco-2 cells. During milk fermentation process, an increase in lactic acid content, a decrease in milk pH, and an increase in the total bacterial count were evidenced. LAB viability in fermented milk during storage remained around 8 log10 CFU/mL. This workflow can be useful for the isolation of new probiotics and the development of fermented milks with probiotic properties to promote host health.